New Coronavirus 2 (SARS-CoV-2) Detection Method from Human Nucleic Acid Sequences Using Capsule Networks - Das, Bihter; Toraman, Suat (Inst Tecnologia Parana, 2023)
The new coronavirus SARS-CoV-2 is an infectious virus with a long incubation period, which was first detected in Wuhan, China, spread all over the world, seriously threatening human life. Therefore, accurate and rapid detection of SARS-CoV-2 is very important for controlling the epidemic and preventing its further spread. Currently, nucleic acid detection makes an important contribution to the prevention and control of SARS-CoV-2. In this study, a new and highly sensitive nucleic acid detection method for SARS-CoV-2 has been proposed. The nucleic acid sequences were digitized by Entropy-based mapping technique. Then, the digitized these sequences were divided into 100-unit sections using the sliding window method and given as input to Capsule Networks.10988 segments (5494 SARS-CoV-2, 5494 normal) are classified with capsule nets. With the proposed method, an accuracy performance of 100% was achieved by using capsule networks to identify SARS-CoV-2 from nucleic acid sequences. The results show that the proposed method successfully identifies SARS-CoV-2 from nucleic acid sequences.
Keywords: SARS-CoV-2; Covid-19; Nucleic acid detection; Capsule networks; Coronavirus